(untitled) (Journal of Health Sciences, 2017)
Introduction: Several studies have reported the incidence of herniated nucleus pulposus (HNP) in some hospitals. Surgery is one of the options in HNP management. HNP surgery results in Aceh have not been reported yet. Therefore, this study reported the HNP surgery in Zainoel Abidin General Hospital, Banda Aceh period 2010-2012. Methods: This was a descriptive retrospective survey conducted in Zainoel Abidin General Hospital Banda Aceh at August-September 2012. Results: The incidence of HNP who underwent surgery was 28 patients. There was no HNP case in the age group I (0-18 years), seven patients (25%) were age group II (19-40 years), and 21 patients (75%) were age group III (over 40 years). Based on HNP location, no HNP located in the L1-L2 and L3-L4, one patient (3.57%) was L2-L3, 20 patients (71.42%) were L4-L5, three patients (10.71%) were L5-S1, and there were four HNP patients in multiple lumbar (14.28%). Laminectomy was the most common type of surgery performed (27 patients or 96.42%), followed by laminotomy (one patients or 3.57%). Conclusion: There was significant association between the incidence of HNP with age, but not with gender. In summary, the most common lumbar disc herniation was in L4-L5. Laminectomy was the most common procedure performed in HNP patient in Aceh.